Effects of winding angles in biaxial ultimate elastic wall stress (UEWS) tests of glass gibre reinforced epoxy (GRE) composite pipes - Mohd Shukry, Abdul Majid, Dr. (Trans Tech Publications, 2014)
Link to publisher's homepage at http://www.ttp.net/